PERAN BADAN PEMBERDAYAAN PEREMPUAN PERLINDUNGAN ANAK DAN KELUARGA BERENCANA DALAM PERLINDUNGAN PEREMPUAN KORBAN KEKERASAN BERBASIS GENDER DI JAWA TENGAH - YANUAR DENY PAMBUDI; Puji Astuti; FITRIYAH . (Journal of Politic and Government Studies, 2016)
ABSTRACTGender-based violence to women is an act of violence which caused suffering to womenon the basis of the victims were women. Violence against women due to gender inequality and injusticecompounded by the unequal power that still exist between men with women. The existence ofpatriarchal ideology that puts the position of women under men also triggers perpetuation of acts ofviolence towards women.In attempt to make protection to women victims of gender-based violence in Central Java,Central Java Provincial Government through the Agency for Child Protection of Women'sEmpowerment and Family Planning (Badan Pemberdayaan Perempuan Perlindungan Anak danKeluarga Berencana/BP3AKB) as the Regional Work Units (Satuan Kerja Perangkat Daerah/SKPD) incharge of the issue of violence against women have been trying to do a variety of ways such ascooperation with state agencies and other non-state role in networking PPT, cooperating with LawEnforcement (APH), as well as with other provinces. The study was conducted using a qualitativeapproach, the research methods used to examine the condition of natural objects (natural setting).The results showed a very dominant role of BP3AKB but has not run optimal because of thelack of gender awareness and commitment which considers that the issue of gender-based violence isan important issue and must be addressed both by law enforcement officials, Regents/Mayors and otherprovinces. Bad service hosted by the service provider at the district / city and the ranks of lawenforcement officers to make the victim into a traumatic and not handled properly. BP3AKB supposedrole is to provide assistance and training to PPT / P2TP2A not run well and many people were not ableto be handled regency / city and referred to the province. It also needs assessment to the regency / cityin Central Java to quickly create a gender-sensitive local regulations such as local regulations on theprotection of women as well as local regulations on gender mainstreaming.Keywords: Violence against women, BP3AKB, Partnership, PPT